CK2 promotes jasmonic acid signaling response by phosphorylating MYC2 in Arabidopsis. Issue 2 (22nd December 2022) - Zhu, Jiang; Wang, Wen-Shu; Yan, Da-Wei; Hong, Li-Wei; Li, Ting-Ting; Gao, Xiang; Yang, Yun-Huang; Ren, Feng; Lu, Ying-Tang; Yuan, Ting-Ting
Abstract: Jasmonic acid (JA) signaling plays a pivotal role in plant development and defense. MYC2 is a master transcription factor in JA signaling, and was found to be phosphorylated and negatively regulated by MAP kinase and receptor-like kinase. However, the kinases that positively regulate MYC2 through phosphorylation and promote MYC2-mediated activation of JA response have not been identified. Here, we identified CK2 as a kinase that phosphorylates MYC2 and thus regulates the JA signaling. CK2 holoenzyme can interact with MYC2 using its regulatory subunits and phosphorylate MYC2 at multiple sites with its catalytic subunits. Inhibition of CK2 activity in a dominant-negative plant line, CK2mut, repressed JA response. On the other hand, increasing CK2 activity by overexpression of CKB4, a regulatory subunit gene of CK2, enhanced JA response in a MYC2-dependent manner. Substitution of the Ser and Thr residues at phosphorylation sites of MYC2 by CK2 with Ala impaired MYC2 function in activating JA response. Further investigations evidenced that CK2 facilitated the JA-induced increase of MYC2 binding to the promoters of JA-responsive genes in vivo . Our study demonstrated that CK2 plays a positive role in JA signaling, and reveals a previously undiscovered mechanism that regulates MYC2 function.